Malocclusion: prevention and treatment during growth and development: Maloklusi: pencegahan dan penanganannya pada masa tumbuh kembang - Yayah Inayah; Sherly Horax; Fajriani; Marhamah; Eka Erwansyah (Makassar Dental Journal PDGI Makassar, 2021)
Malocclusion is a common condition in the world's population but is not considered as a normal condition. A normal dentofacial development depends on the normal function of the muscles around the mouth, the balance between the muscles of the lips, cheeks from the outside of the dental arch and the inside of the tongue needs to be maintained. The imbalance of the three orofa-cial muscles will affect the development of dentofacial structures. Malocclusion occurs due to several factors including genetic factors and environmental factors. Prevention of malocclusion can be done in several ways, namely eliminating prolonged bad habits and improving nutrition during pregnancy. If malocclusion has occurred, treatment is carried out as early as possible so as not to aggravate the malocclusion.